2010
DOI: 10.1287/mnsc.1090.1137
|View full text |Cite
|
Sign up to set email alerts
|

Operational Flexibility and Financial Hedging: Complements or Substitutes?

Abstract: W e consider a firm that invests in capacity under demand uncertainty and thus faces two related but distinct types of risk: mismatch between capacity and demand and profit variability. Whereas mismatch risk can be mitigated with greater operational flexibility, profit variability can be reduced through financial hedging. We show that the relationship between these two risk mitigating strategies depends on the type of flexibility: Product flexibility and financial hedging tend to be complements (substitutes)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(100 citation statements)
references
References 36 publications
(37 reference statements)
1
98
1
Order By: Relevance
“…And how much flexibility is needed to effectively match demand and supply? The extant literature on flexibility refers to the ability of a resource to process multiple types of products as mix- (Chod et al 2010), process- (Sethi and Sethi 1990), product- (Fine and Freund 1990) or scope-flexibility (Van Mieghem 2008). Substantial progress has been made in our understanding of flexibility over the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…And how much flexibility is needed to effectively match demand and supply? The extant literature on flexibility refers to the ability of a resource to process multiple types of products as mix- (Chod et al 2010), process- (Sethi and Sethi 1990), product- (Fine and Freund 1990) or scope-flexibility (Van Mieghem 2008). Substantial progress has been made in our understanding of flexibility over the last 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting work looks into the complementarity/substitution aspects of financial hedges and operational risk mitigation strategies (see Chod et al 2010). However, the fundamental question if financial hedging should be used for managing operational risks was left to corporate finance theory insights mostly informed by single firm and financial friction justifications (for an exemplary reference, and reference therein, see Froot et al 1993).…”
Section: Integrated Risk Managementmentioning
confidence: 99%
“…Nevertheless, this gap in the research literature received a greater amount of attention only recently. Chod, Rudi, and Van Mieghem (2010) investigated the relationship between financial hedging and product flexibility under uncertain demands. They showed that product flexibility and financial hedging can be both complements and substitutes depending on the prevailing demand correlations.…”
Section: Literature Reviewmentioning
confidence: 99%